Nitrogen isotopic composition of free Gly in aerosols at a forest site. (1st February 2020) - Zhu, Ren-guo; Xiao, Hua-Yun; Lv, Zhe; Xiao, Hao; Zhang, Zhongyi; zheng, Nengjian; Xiao, Hongwei
Abstract: The nitrogen isotope composition of free glycine (δ 15 NF-Gly ) in atmospheric particulates from different sources was measured to explore whether δ 15 NF-Gly could be used to indicate the sources of particulates. We found that the δ 15 NF-Gly released by biomass combustion (range: +16.9 to +27.3‰) was significantly higher than that from natural sources (up to 21.6‰). The concentration of free Gly in particulates released from fossil fuel combustion (bituminite combustion and vehicle emission) was very low. These results provided the possibility for using the δ 15 NF-Gly values in aerosol to distinguish biomass combustion from natural sources. In the field, a high correlation between the free Gly concentrations in aerosol and nonsea salt potassium (nss-K + ) was observed. The δ 15 NF-Gly values showed the same temporal pattern with fire points and a link between the δ 15 NF-Gly values and nss-K + levels was found. These results suggested that the δ 15 NF-Gly value in aerosol might be a good indicator for biomass burning. Graphical abstract: Image 1 Highlights: Nitrogen isotope of free Gly in total suspended particulates were first reported. Nitrogen isotope of free Gly in aerosol might be useful for tracing biomass burning. Bituminous combustion and vehicle emissions may not be the source of free Gly.